Clinical Results of Oxidized Zirconium Femoral Component in TKA. A Review of Long-Term Survival: Review Article. Issue 1 (February 2017) - Civinini, Roberto; Matassi, Fabrizio; Carulli, Christian; Sirleo, Luigi; Lepri, Andrea Cozzi; Innocenti, Massimo
Background: Oxidized zirconium (OxZr) femoral component for total knee arthroplasty (TKA) have been introduced in an attempt to reduce polyethylene wear and secondary osteolysis and improve longevity of implants. Questions/Purposes: We reviewed clinical studies in literature evaluating OxZr femoral component for TKA. The aim of this review was to evaluate the clinical outcome and survival rate of TKA with an OxZr femoral component. Methods: A review of the existing literature was undertaken to collect data on the OxZr femoral component in order to provide a better understanding of its performance. Of 34 studies published in the literature, 8 met the eligibility criteria and were included in the final analysis. Results: Findings indicated that the mean Knee Society knee score improved in all series from preoperative to postoperative evaluation. The postoperative Knee Society knee score reported range from 84 to 95 and mean postoperative Knee Society functional score range from 74 to 90. The revision rate with this implant is low with up to 12.6 years of follow-up, with three revisions in total. The survival rate ranged from 100–98.7% at 5–7 years to 97.8% at 10 years. Conclusions: Excellent clinical outcome and high survival rate has been demonstrated for OxZr femoral component in TKA. No adverse reaction has been described for this new material.